Political Capture of Decentralization : Vote-Buying through Grants-Financed Local Jurisdictions - Khemani, Stuti (2012)
A recent trend in decentralization in several large and diverse countries is the creation of local jurisdictions below the regional level -- municipalities, towns, and villages -- whose spending is almost exclusively financed by grants from both regional and national governments. This paper argues that such grants-financed decentralization enables politicians to target benefits to pivotal voters and organized interest groups in exchange for political support. Decentralization, in this model, is subject to political capture, facilitating vote-buying, patronage, or pork-barrel projects, at the expense of effective provision of broad public goods. There is anecdotal evidence on local politics in several large countries that is consistent with this theory. The paper explores its implications for international development programs in support of decentralization.